1998
DOI: 10.1161/01.cir.97.10.965
|View full text |Cite
|
Sign up to set email alerts
|

Significance of Paroxysmal Atrial Fibrillation Complicating Acute Myocardial Infarction in the Thrombolytic Era

Abstract: Background-Paroxysmal atrial fibrillation (PAF) is considered a frequent complication of acute myocardial infarction (AMI), associated with increased in-hospital and long-term mortality rates. This notion is based on data collected before thrombolysis and additional modern methods of treatment became widely available, and no information is available on the significance of PAF in the general population with AMI in the thrombolytic era. The aim of the present study was to define the incidence, associated clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
53
1
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 136 publications
(68 citation statements)
references
References 31 publications
8
53
1
3
Order By: Relevance
“…In accordance with previous studies,4 6 we noted that a worse Killip class and reduced left ventricular systolic function were independent predictors of AF, suggesting that elevated left atrial filling pressures are an important underlying mechanism in the development of AF. In addition, we observed a positive graded independent association between FMR severity and new-onset AF.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In accordance with previous studies,4 6 we noted that a worse Killip class and reduced left ventricular systolic function were independent predictors of AF, suggesting that elevated left atrial filling pressures are an important underlying mechanism in the development of AF. In addition, we observed a positive graded independent association between FMR severity and new-onset AF.…”
Section: Discussionsupporting
confidence: 92%
“…New-onset AF is a frequent arrhythmia complicating AMI1–4 6 15 and is associated with an adverse prognosis 2. The mechanisms that promote the development of AF in the AMI setting are complex and often multifactorial.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies [1,10,11,12,13] have shown that AMI patients with AF had worse baseline characteristics, more complicated hospital course, and worse outcome than those without AF. In our earlier study [4], we found that overall AF was not an independent predictor of in-hospital and 7-year mortality.…”
Section: Discussionmentioning
confidence: 99%